Pengaruh Perubahan Kadar pH Air Dengan Optimalisai Ukuran dan Suhu Aktivasi Serbuk Cangkang Siput Hisap (Cerithidea Obtusa) Sebaga Media Adsorben - Candra Permana, Agi candra permana; Juanda, Juanda; Anggry, Adhe (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The demand for clean water continues to increase along with population growth. Therefore, it is important to improve water quality to meet the demand for clean water supply. There are three methods that can be used in the water purification process, namely filtration, sedimentation, and adsorption. Clam shell waste contains calcium carbonate (CaCO3) with a percentage of 98%. This content can be used as an adsorption media. The purpose of this research is to utilize gold snail shell waste for activation at mesh size and temperature by determining the most optimum value. The results of making adsorbents will be tested on borehole water at the Bangka Belitung State Manufacturing Polytechnic to study changes in the degree of acidity of water pH. The research was conducted using the Taguchi method, where the process parameters were mesh size and activation temperature. The parameters were then adjusted with the OA L_9 algorithm for three repetitions. Based on the results of the research and test data processing that has been done, it is concluded that the activation temperature is the highest influence in the process of making adsorbents. Optimal results were obtained at a powder size of 150 mesh (109 μm) and at an activation temperature of 700o C. With a percent contribution value on mesh size of 3.42% and activation temperature of 94.32%. It can be concluded that activation temperature is the highest influence in the process of making adsorbents.